Embriogenesis somatik dari pucuk tunas tanaman kurma (Phoenix dactylifera L.) Somatic embryogenesis from shoot tip of date palm (Phoenix dactylifera L.)) - Rizka Tamania SAPTARI; . SUMARYONO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2018)
Date palm (Phoenix dactylifera L.) is the most important crop in the dry areas of the Middle East and North Africa. This palm has been introduced to many countries but has not been grown commercially in Indonesia. Date palm propaga-tion by seeds is easy but its progenies are varied and a half of them are male trees that will not produce fruits. Meanwhile, the propagation by offshoots is impractical and technically difficult. Tissue culture makes it possible to massproduce of genetically identicalsuperior date palms. This research aimed to develop somatic embryogenesis (SE) of date palm using shoot tipand young leaves of date palm seedling as explants. Steps on somatic embryogenesis are explant sterilization, callus initiation and proliferation, somatic embryos induction and maturation, and plantlets matura-tion and rooting. Calli emerged from shoot tip explants after 9 weeks of culture in a modified MS medium supplemented with 10 mg/L 2,4-D, 1 mg/L or 3 mg/L 2-iP, and 1.5 g/L active charcoal. The callus was able to bear somatic embryo in the modified MS medium without hormones. Somatic embryos then developed into plantlets, and roots of plantlets were effectively initiated in the medium supplemented with 0.5 mg/L NAA and 1 mg/L IBA.[Keywords:sterilization, callogenesis, somatic embryo induction, plantlet rooting, clonal propagation]. Abstrak Tanaman kurma (Phoenix dactyliferaL.) merupakan tanaman terpenting di wilayah kering Timur Tengah dan Afrika Utara. Palma ini telah menyebar ke banyak negara, namun belum ditanam secara komersial di Indonesia. Perbanyakan kurma dengan biji sangat mudah tetapi turunannya sangat beragam dan setengahnya merupakan tanaman jantan yang tidak berbuah. Perbanyakan dengan anakan (offshoots) secara komersial tidak praktis dan relatif sulit. Kultur jaringan memungkinkan untuk dihasilkan secara massal bibit tanaman kurma varietas unggul yang secara genetik seragam. Penelitian ini bertujuan untuk mengembangkan embriogenesis somatik menggunakan eksplan pucuk tunasdan daun muda dari bibit tanaman kurma. Pengembangan embriogenesis somatik terdiri dari tahap sterilisasi eksplan, inisiasi dan proliferasi kalus, induksi dan maturasi embrio somatik, serta pembesaran dan pembentukan akar planlet. Kalus terbentuk dari eksplan pucuk tunassetelah 9 minggu dikultur pada medium MS modifikasi yang ditambahkan 2,4-D 10 mg/L, 2-iP 1 mg/L atau 3 mg/L, dan arang aktif 1,5 g/L.Kalus berhasil diinduksi menghasilkanembrio somatik pada medium MS modifikasi tanpa penggunaan hormon. Embrio somatik kemudian berkembang hingga menjadi planlet, dan akar planlet secara efektif terinisiasipada medium yang ditambahkan NAA 0,5 mg/L dan IBA1 mg/L. [Kata kunci :sterilisasi, kalogenesis, induksi embrio somatik, pengakaran planlet, propagasi klonal].